Hubungan Kepatuhan Diet dengan Kejadian Hiperglikemia pada Pasien Diabetes Melitus di Wilayah Kerja Puskesmas Biru Kab.Bone - Najman Najman; Musdalipa Musdalipa (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Diabetes Mellitus (DM) is a chronic metabolic disease characterized by elevated blood glucose levels (hyperglycemia) resulting from impaired insulin secretion, insulin action, or both. Non-adherence to dietary recommendations is one of the factors that may trigger hyperglycemia in patients with DM, as poor dietary adherence can increase blood glucose levels (random blood glucose [RBG] > 200 mg/dL). According to the World Health Organization (WHO), approximately 422 million people worldwide have diabetes mellitus, particularly in low- and middle-income countries, including Indonesia, with approximately 1.6 million deaths occurring each year (World Health Organization, 2018). This study aimed to determine the relationship between dietary adherence and the incidence of hyperglycemia. The study was conducted in July 2026 using a quasi-experimental design with a one-group pretest-posttest design. The results of the study conducted in one of the working areas of Biru Public Health Center showed that some community members adhered to the recommended diet, while others did not, which may affect blood glucose levels. The level of dietary adherence among patients with DM was reported to be 65%; however, only 19% of patients actually followed the recommended diet. The findings are consistent with previous research indicating that maintaining normal blood glucose levels is important to prevent the effects of elevated blood glucose, including glucose loss through urine.